ETHICS OF CARE SEBAGAI MALE FEMINIST TERHADAP PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Yana Suryana (Kajian Hukum, 2018)
Male concern as male feminists is a quite interesting study. This study is important to show the nature of the concern and seriousness of male feminists in protecting the legal rights of women victims of domestic violence. This study was conducted by studying literature and displaying supporting data in quantitative form. The results of the study showed that male feminists did not have the same ethics of care as women in cases of domestic violence. Ethics of care as a male feminist towards women who correct problems in the household cannot really show their concern as women's concerns. Based on these assessments can be discussed. First, every process must be more about women. Second, more assess women in prosecuting cases of domestic violence.Keywords : Ethics of care, women, male feminist